COMMUNITY SOCIAL-ECOLOGY DYNAMICS ON MADAK CULTURE OF COASTAL REGION, WEST SUMBAWA - A Lidya Tania; Fredinan Yulianda; Luky Adrianto (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2014)
ABSTRACT Madak activity is a local word for the people of Sumbawa to collect marine biota in tidal area during the low tide. The purpose of this study was to determine social change in communities of West Sumbawa for doing Madak culture. The study was conducted for 2 months in ​​West Sumbawa. Data were collected through observation, questionnaire, and interviewing the Madak people. It seemed that Madak culture changed totally, especially in daily actvities. In the past, they used tools that were environmentally friendly. However, during this study, they tended to damage coastal environment by flipping the reef. Keywords: Social, ecology, Madak culture, west Sumbawa